From Memory to Marble : The historical frieze of the Voortrekker Monument Part II: The Scenes - Michael Schneider, Rolf; Rankin, Elizabeth (2020)
The book is a rare case study of the dynamics, processes and shifts around the creation and reading of one of the world’s major monuments, through all the processes of its design and making. The frieze which represents the Great Trek and Voortrekker occupation of South Africa (1835-52) is one of the largest of its kind. The key question is how, a century later, were eighteen years of Voortrekker memory transformed into a 92-metre marble frieze?...